Mukjizat Al-Qur'an yang tak terbantahkan / Yusuf Al-Hajj Ahmad; alih bahasa, Zulhamid, Putri Aria Miranda; editor, Firman Pramudya - AHMAD, Yusuf Al-Hajj; Zulhamid; Putri Aria Miranda; Firman Pramudya (Aqwam, 2016)
382 hlm. : ilus. ; 23 cm.